Design for SLS according to fib Model Code 2010. (3rd June 2013) - Balázs, György L.; Bisch, Philippe; Borosnyói, Adorján; Burdet, Olivier; Burns, Clare; Ceroni, Francesca; Cervenka, Vladimir; Chiorino, Mario A.; Debernardi, Piergiorgio; Eckfeldt, Lars; El‐Badry, Mamdouh; Fehling, Ekkehard; et al.
Abstract This paper provides an overview of serviceability specifications given by the fib Model Code for Concrete Structures 2010 (fib MC2010 [1]). First, the reasons behind crack control and deflection control are discussed, then specific design rules are provided. Simple rules as well as detailed models are also presented. Numerical examples are provided in order to assist in the application of the design recommendations for crack control and deflection control (reinforced and prestressed concrete elements). Simple rules mean indirect control of cracking or deflections without calculations. Indirect crack control may include limitation of stresses and selection of maximum bar diameter or maximum bar spacing. Indirect deflection control normally means limiting the span‐to‐depth ratio. Detailed models are based on physical and mathematical approaches to cracking and deflections. The design crack width is expressed as the maximum bond transfer length multiplied by the mean strain between cracks. Deflection analysis can be provided by integrating curvatures or by using a simplified or refined method. Vibrations and numerical modelling of cracking are also briefly discussed.